ChemInform Abstract: RFe2MgxAl8‐x (R: La—Nd and Sm; x ≈ 0.8): Flux Synthesis, Structure, Magnetic and Electrical Properties. Issue 40 (October 2015) - Ma, Xiaowei; Chai, Ping; Chen, Banghao; Lochner, Eric; Latturner, Susan E.
Abstract Single crystals of Mg‐substituted CeFe2Al8‐type intermetallics LnFe2MgxAl8‐x (Ln: La—Nd, Sm; x ≤ 1) are grown by reaction of Fe and Ln in a 1:1 Mg/Al reactive flux (steel capsules in evacuated silica tubes, 950 °C, 5 h; controlled cooling).